If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t + 7 + -13 = -4 Reorder the terms: 7 + -13 + t = -4 Combine like terms: 7 + -13 = -6 -6 + t = -4 Solving -6 + t = -4 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + t = -4 + 6 Combine like terms: -6 + 6 = 0 0 + t = -4 + 6 t = -4 + 6 Combine like terms: -4 + 6 = 2 t = 2 Simplifying t = 2
| sin(3x-30)=0.6 | | 4A-20=22 | | -6(7+X)=-42 | | 7.3+z=60 | | 10a+15b=2x | | 2x+10=-3x | | 2x+5*3=11 | | 2ln(2*x+1)-3ln(x+1)+ln(x+1)=0 | | 3x+18=3x+34 | | 2(4-5x)=7-5(x-2) | | 20+1d=30+.5d | | 4n+3m=11 | | -30=5w+5 | | 64=9u-u | | 103+5x=63 | | 2(x)=54 | | x/-6=120 | | 2y+16=48 | | 2x-2-3=21-34x | | 31+4x=86 | | xln(x)-1=0 | | -54-8x=2x | | (1.09^x)/50 | | 4/5/5/4= | | v=1/3*b*h | | 7n-3n=3n+15 | | 3-12x+18=33 | | 9x-10y=24 | | -4-8=4(-3n+2) | | 9x-11=3x+8 | | 4x(3-y)=0 | | x+5(x-2)=8 |